2021
DOI: 10.3390/su13168793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climate Changes on Renewable Production in the Mediterranean Climate: Case Study of the Energy Retrofit for a Detached House

Abstract: One of the strategies of the European Green Deal is the increment of renewable integration in the civil sector and the mitigation of the impact of climate change. With a statistical and critical approach, the paper analyzes these aspects by means of a case study simulated in a cooling dominated climate. It consists of a single-family house representative of the 1980s Italian building stock. Starting from data monitored between 2015 and 2020, a weather file was built with different methodologies. The first obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Climate change affects also the production of energy from renewable energy sources. In southern Italy, De Masi et al [10] found an increase in electricity production frm PV systems using future weather data, but they also found a greater increse in cooling energy demand. However, climatic change has an effect also on the internal conditions in buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change affects also the production of energy from renewable energy sources. In southern Italy, De Masi et al [10] found an increase in electricity production frm PV systems using future weather data, but they also found a greater increse in cooling energy demand. However, climatic change has an effect also on the internal conditions in buildings.…”
Section: Introductionmentioning
confidence: 99%